SIMULATION OF PLASMOTRON NOZZLE COOLING SYSTEM FOR SURFACE HARDENING AND NANOSTRUCTURING - Мазур, Владислав; Микула, Владимир (SWorldJournal, 2021)
The work is devoted to the issues of improving and optimizing the cooling system of the indirect action plasmatron nozzle. The qualitative and quantitative characteristics of hardening, as well as the service life of plasmatrons largely depend on the pro